Perspectives on the geography of intolerance: Racist attitudes and experience of racism in Melbourne, Australia. (March 2016) - Forrest, James; Elias, Amanuel; Paradies, Yin
Highlights: Deconstruction of racist attitudes assists understanding experiences of racism. A new approach to attitude–experience interaction within two embedded samples is deployed. Host society racist attitudes are reflected in out-group status attribution. Out-group status varies by locality according to the nature of the ethnic mix. Local ethnic and socio-demographic profiles point to tailored anti-racism strategies. Abstract: Given the challenge presented by worsening racial and religious relations in many western countries around the world, a closer look at the interplay between racist attitudes among potential perpetrators and experiences of racism among likely targets, focusing on out-group status, can better inform the dynamics of culturally diverse societies. Melbourne, Australia is ideal for such an analysis given its highly diverse population. Building on recent scholarship detailing a new approach to examining the attitude–experience relationship, we add an important spatial dimension by investigating how patterns of association vary spatially within specific localities over and above citywide effects. Findings indicate significant associations between racist attitudes and experience of discrimination at the citywide and, in distinct ways, at the local (Local Government Area) level. Such relationships are shaped by socio-demographic and ethnic diversity profiles, embodying attribution and degree of out-group status, in complex and nuanced ways.